Mengkaji Ulang Strategi Penginjilan Paulus dalam Kisah Para Rasul19: 1-11 dan Relevansinya pada Masa Kini - Sriwijayanto, Wahyudi (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
Evangelism is preaching the Gospel to everyone. The background to this research is the lack of enthusiasm in preaching the Gospel and the evangelism strategies carried out by the church. The purpose of this article is to review Paul's evangelistic strategy in Acts 19 verses 1 to 11 and its application to the church today. This article uses a biblical studies research method, namely the study of words from the original language. Several words studied and related to the topic discussed. The result of this research is Paul's evangelism strategy in Acts 19:1-11. First, dare to visit, second, teach about Christ, and third, make disciples or be left behind.